+0  
 
0
134
3
avatar+18 

6x-3y=9

y=4x-1 

whats the answer?

robswag  Apr 18, 2017
Sort: 

2+0 Answers

 #1
avatar+80 
+1

the answer is -1...push heart plz :).  You have to use substitution to get the answer...in order to get x you have to replace part of the first formula with the second :)

wgunningham  Apr 18, 2017
 #2
avatar
-1

\(6x-3y=9 \)                   |    \(/3\)

\(2x-y=3\)                   |    \(y=4x-1\)

\(2x-4x+1=3\)

\(-2x+1=3\)                   |   \(-1\)

\(-2x=2\)                   |   \(/-2\)

\(x=-1\)

 

\(y=4x-1\)                   |   \(x=-1\)

\(y=4*(-1)-1\)

\(y=-5\)

 

Should be the right solution. (I hope I made no mistakes)

Guest Apr 18, 2017
edited by Guest  Apr 18, 2017

11 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details